A new species of freshwater crab of the genus Huananpotamon Dai & Ng, 1994 (Decapoda: Brachyura: Potamidae) from northern Jiangxi, China - Wang, Ruxiao; Pan, Da; Sun, Hongying (Zootaxa, 2024)
A morphologically distinct new species of Huananpotamon Dai & Ng, 1994, is described from Yugan County, Shangrao City, Jiangxi Province, China. The new species, H. amicitiae sp. nov., can be differentiated from its closest congeners by structure of the epibranchial tooth, external orbital angle and male first gonopod. A phylogenetic analysis based on mitochondrial 16S rDNA sequences supports the recognition of the new species.